Transposition of Great Arteries: New Insights into the Pathogenesis - Unolt, Marta; Putotto, Carolina; Silvestri, Lucia M.; Marino, Dario; Scarabotti, Alessia; Massaccesi, Valerio; Caiaro, Angela; Versacci, Paolo; Marino, Bruno (Frontiers in Pediatrics, 2013)
Transposition of great arteries (TGA) is one of the most common and severe congenital heart diseases (CHD). It is also one of the most mysterious CHD because it has no precedent in phylogenetic and ontogenetic development, it does not represent an alternative physiological model of blood circulation and its etiology and morphogenesis are still largely unknown. However, recent epidemiologic, experimental and genetic data suggest new insights into the pathogenesis. TGA is very rarely associated with the most frequent genetic syndromes, such as Turner, Noonan, Williams or Marfan syndromes, and in Down syndrome, it is virtually absent. The only genetic syndrome with a strong relation with TGA is Heterotaxy. Moreover, TGA is rather frequent in cases of isolated dextrocardia with situs solitus, showing link with defect of visceral situs. In lateralization defects TGA is frequently associated with asplenia syndrome. Nowadays, the most reliable method to induce TGA consists in treating pregnant mice with retinoic acid or with retinoic acid inhibitors. Following such treatment not only cases of TGA with d-ventricular loop have been registered, but also some cases of congenitally corrected transposition of great arteries (CCTGA). In another experiment, the embryos of mice treated with retinoic acid in day 6.5 presented Heterotaxy, suggesting a relationship among these morphologically different CHD. In some families, beside TGA cases, there were first-degree relatives with CCTGA. This data suggest that monogenic inheritance with a variable phenotypic expression could explain the familial aggregation of TGA and CCTGA. In some of these families we previously found multiple mutations in laterality genes including Nodal and ZIC3, confirming a pathogenetic relation between TGA and Heterotaxy. These overall data suggest to include TGA in the pathogenetic group of laterality defects instead of conotruncal abnormalities due to ectomesenchymal tissue migration.